Antimicrobial Substance Produced by Lactobacillus sp. TGR-2 Isolated From Growol - Titiek F. Djaafaru; Endang S. Rahayu; Djoko Wibowo; Slamet Sudarmadji (Indonesian Food and Nutrition Progress, 1996)
Lactic acid bacteria strain TGR-2 was isolated from growol (fermented raw cassava) and then identified as Lactobacillus sp. TGR-2. According to results of the turbidimetric assay, the neutralized supernatant of Lac¬tobacillus sp. TGR-2 were able to inhibit the growth of spoilage and pathogenic bacteria, i.e., Staphylococcus aureus FNCC 0047, Salmonella iyphimurium FNCC 0050, Escherichia coli FNCC 0091, Bacillus cereus FNCC 0057, and Morganella morganii FNCC 0122. The antimicrobial activity of neutralized supernatant of Lactobacillus sp. TGR-2 was stable at room tempera¬ture for 60 min, pH 3-8; heating 98 °C for 30 min, pH 3-8; 121 °C for 15 min, pH 3-8; storage at 4 °C for 21 days, p1-1 6.5. The third fraction obtained from purified of supernatant of Lactobacillus sp. TGR-2 by gel filtra¬tion which possessed the molecular weight 14,000 Dalton has a bactericidal effect on the growth of S. aureus.